Nyekar Di Tinjau Dari Pendekatan Filologis Study Islam - Putri Hana; Ahmad Tufani; Dede Muhammad Hidayat; Muhammad Syaifullah (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
. In Indonesia, there are various cultures and traditions, making Indonesia a beautiful country with traditions and culture. Nyekar is a tradition in Indonesia and is often practiced by Indonesian people, especially Javanese people. Nyekar is an activity of sowing flowers accompanied by prayer, tahlil, and some verses from the Koran. This nyekar tradition is generally carried out by people before Ramadhan. In this research the aim is to find out the meaning and tradition of nyekar through a philological approach in Islamic studies. In this research the researcher used library research with a descriptive qualitative approach. However, the main problem in this research is still based on the empirical answers found in this research. The results of this research are analyzing the nyekar tradition from several aspects through reviewing the philological approach to Islamic studies. The following aspects are analyzed: 1) Ancient Islamic texts. 2) The tradition of visiting graves. 3) Prayer for the deceased. In the nyekar tradition itself, it has very long historical roots and is rich in symbolic meaning. Therefore, the philological review carried out by this researcher is to make it easier to understand the origins, meaning or cultural values ​​contained in these nyekar activities.